Experimental Study on Lateral-Load-Resisting Capacity of Masonry-Infilled Reinforced Concrete Frames - Minjae Kim; Eunjong Yu (Applied Sciences, 2021)
In this study, an experimental program was performed on masonry-infilled frame specimens with varied construction precision and masonry thickness. A total of five portal frame specimens, which consist of four masonry-infilled frames and a bare frame, were tested, and the results were analyzed to investigate the effects of construction precision and interaction between the masonry infill and the frame. The test results indicated that the gap in the masonry infill decreased strength by 75% to 80% and stiffness by 55% to 70%. A comparison between the measured and predicted peak strength using the current code shows that the code equations underestimate the strength by up to 70%. This is due to the fact that the contribution of friction in shear resistance of the masonry wall is actually ignored in the current code since no adequate method for estimating the normal force is provided. In addition, reflecting the observation that the failure mode of the columns changed to shear failure when thick masonry walls were used, a mechanical model that can explain the shear failure and enables the estimation of maximum strength was proposed. The maximum strengths of the specimens calculated using the proposed model were in good agreement with the experimental results.